PEMINJAMAN DAN PENYERAPAN KOSAKATA KULINER DALAM BAHASA INDONESIA: REPRESENTASI BUDAYA MILENIAL DAN Z - Yermia Nugroho Agung Wibowo; Syamsul Sodiq; Heny Subandiyah; Mixghan Norman Antono (Universitas Negeri Surabaya, 2026)
Culinary vocabulary continues to develop along with the development of culinary arts in Indonesia. This vocabulary is used by the public and has become a popular vocabulary, especially vocabulary related to food, along with the interest of millennials and Z generations in culinary that is